Race, Ethnic, and Sex Differences in Prevalence of and Trends in Hallucinogen Consumption Among Lifetime Users in the United States Between 2015 and 2019 - Davis, Alan K.; Arterberry, Brooke J.; Xin, Yitong; Agin-Liebes, Gabrielle; Schwarting, Corrine; Williams, Monnica T. (Frontiers in Epidemiology, 2022)
Background: The current study is one of the first to examine race, ethnic, and sex differences in the prevalence of and trends in hallucinogen use among lifetime users in the United States. Methods: Data came from the 2015-2019 National Survey on Drug Use and Health and included respondent’s reporting ever-using hallucinogens (n=41,060; female=40.4%). Descriptive and multinomial logistic regression analyses were conducted in Stata. Results: Highest prevalence of past year hallucinogen use was among Asian females (35.06%), which was two-or-more times larger than prevalence of past year use among White males/females and Native American males. More than half of White males/females, Multiracial males, and Hispanic males reported had ever-used psilocybin or LSD, whereas less than one-quarter of Black males/females reported lifetime psilocybin use, and less than a third of Black females reported lifetime LSD use. Native American males had the lowest prevalence of lifetime MDMA use (17.62%-33.30%) but had the highest lifetime prevalence of peyote use (40.37%-53.24%). Pacific Islander males had the highest prevalence of lifetime mescaline use (28.27%), and lifetime DMT use was highest among Pacific Islander males/females (15.68%-38.58%). Black, Asian, and Multiracial people had greater odds of past-year (ORs=1.20-2.02; ps<.05) and past-month (ORs=1.39-2.06; ps<.05) hallucinogen use compared to White people. Females had lower odds of past-year (OR=0.79; ps<.05), past-month (OR=0.78; ps<.05) hallucinogen use compared to males, except for lifetime use of MDMA (OR=1.29; ps<.05). Conclusions: These findings should inform public health initiatives regarding potential benefits and risks of hallucinogen use among racial/ethnic groups and women.